2020
DOI: 10.1186/s12872-020-01675-y
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neuropathy following venoarterial-extracorporeal membrane oxygenation therapy: a case report

Abstract: Background Although life-threatening complications of extracorporeal membrane oxygenation (ECMO) are well described, non-life threatening complications are less known. Herein, we report a case of femoral neuropathy (FN) due to nerve compression caused by cannula compression and deep vein thrombosis (DVT) after successful ECMO therapy, which seriously undermined one’s quality of life. Case presentation A 70-year old male presented to the emergency department for chest pain. The patient had cardiac arrest befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Suboptimal knee positioning can enhance the compression of the fibular nerve at the fibular head level [ 15 , 19 ]. Continuous use of an automatically cycled blood pressure cuff can cause radial nerve injury [ 19 , 40 ]. We speculated that unexpected compressions or stretching associated with positioning or medical procedures might have resulted in the peripheral nerve injuries in our cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suboptimal knee positioning can enhance the compression of the fibular nerve at the fibular head level [ 15 , 19 ]. Continuous use of an automatically cycled blood pressure cuff can cause radial nerve injury [ 19 , 40 ]. We speculated that unexpected compressions or stretching associated with positioning or medical procedures might have resulted in the peripheral nerve injuries in our cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intensive respiratory care and positionings, other procedures can also cause peripheral nerve injuries. ECMO, for example, is reported as a possible cause of lower limb peripheral nerve injuries, although no COVID-19 cases have been reported [ 40 , 41 , 42 , 43 ]. According to the literature, bulky cannulas placed on the femoral artery and vein can damage the femoral nerve [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, femoral neuropathy has been described as a complication following extracorporeal membrane oxygenation (ECMO) and may become more prevalent as patients are treated with ECMO for COVID-19. 62…”
Section: Future Trendsmentioning
confidence: 99%
“…The authors suggested that prolonged immobility or impairment in circulation due to microvascular thrombosis or microembolization may have caused foot drop. Jang et al reported a case of femoral neuropathy after veno-arterial ECMO therapy and postulated that direct nerve compression from the ECMO cannula may have caused neuropathy ( 18 ). Despite these hypotheses, the exact cause of unilateral limb weakness after ECMO therapy in the absence of limb ischemia is still uncertain, and further studies are required to elucidate the mechanism of neuropathy.…”
Section: Discussionmentioning
confidence: 99%